Responsible leadership: a comparative study between Peruvian national and private universities - Vásquez Pauca, Mario José (2022)
Purpose: A university community that works for and supports students along their developmental trajectory through responsible leadership is important for a sustainable and accountable educational environment. Public and private institutions differ in their student leadership responsibilities. In light of this, the objective of this study is to analyze the level of responsible leadership between public and private colleges in Peru in 2022. Design/Methodology/Approach: This study employs quantitative and descriptive-comparative research methods. This study's sample included 459 instructors from six public and private institutions in Peru. The survey-based method was used to collect data on responsible education leadership. Findings: The study's findings emphasized the importance of responsible leadership in colleges. This study shows that private institutions in Peru have a better level of responsible leadership than governmental universities. Practical Implications: This study underlines that strong leadership should always seek innovation in the field of education, keeping current with the most recent achievements and collecting feedback from university teachers and students. To obtain a higher education level, institutions should therefore foster responsible leadership. Originality/value: This research contributes to a previously unexplored section of the literary canon. Several prior studies have researched responsible leadership; however, the context of the present study is neglected by those prior studies. Previous research neglected the significance of responsible leadership within universities. Rarely have past studies compared national universities in Peru to private ones. Therefore, this work made a substantial contribution to the corpus of knowledge.